2011
DOI: 10.1007/s00277-011-1299-8
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic bone marrow transplantation compared to peripheral blood stem cell transplantation for the treatment of hematologic malignancies: a meta-analysis based on time-to-event data from randomized controlled trials

Abstract: Controversy remains regarding the transplant outcomes of human leukocyte antigen-identical related bone marrow transplantation (BMT) and peripheral blood stem cell transplantation (PBSCT) for the treatment of patients with hematological malignancies. To provide an estimate of the effect of BMT and PBSCT on clinical outcomes in patients with hematological malignancies, we conducted a meta-analysis based on time-to-event data from 17 randomized controlled trials. PubMed, EMBASE, and Cochrane Central Register of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 49 publications
1
18
0
1
Order By: Relevance
“…In addition to intensification of the preparative regimen dose as a strategy to reduce the risk of recurrence in high-risk malignancies, we also postulated that the use of PBSC, instead of BM, as the stem cell source may provide additional benefit in patients with high-risk malignancies. The use of PBSC, although associated with a higher incidence of chronic GVHD, has also been correlated with a significantly decreased risk of relapse in several large meta-analyses [20][21][22]. In our previous study, we provided transplantation to 20 patients with high-risk hematologic malignancies, including 11 (55%) who were not in remission at the time of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to intensification of the preparative regimen dose as a strategy to reduce the risk of recurrence in high-risk malignancies, we also postulated that the use of PBSC, instead of BM, as the stem cell source may provide additional benefit in patients with high-risk malignancies. The use of PBSC, although associated with a higher incidence of chronic GVHD, has also been correlated with a significantly decreased risk of relapse in several large meta-analyses [20][21][22]. In our previous study, we provided transplantation to 20 patients with high-risk hematologic malignancies, including 11 (55%) who were not in remission at the time of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Graft-versus-host disease (GVHD) continues to be amajor cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (AHSCT) [14]. Methods to prevent GVHD in most centers consist of a combination of methotrexate (MTX) and a calcineurin inhibitor, either cyclosporine A (CSA) or tacrolimus (Tac).…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, the most common haematological disorders associated with graft versus host disease were acute and chronic leukemia. A meta-analysis done by Chang et al [31] also identified the aforementioned three most common haematological disorders associated with GvHD. Recently, peripheral blood stem cells have gained acceptance they and in 71% of allogeneic transplants, are being used as stem cell source.…”
Section: Discussionmentioning
confidence: 99%